Revealing the Student Philanthropy Movement in the Midst of the COVID-19 Pandemic - Anita Puji Astutik; Safitri Khoirinindyah; Anis Farihah (Postgraduate Program Magister Pendidikan Agama Islam, 2021)
The philanthropic movement aims to increase student knowledge and involvement in allocating funds to support social activism. At the time of the Covid-19 outbreak, philanthropy-based da'wah was a common form of da'wah carried out by students with the Muhammadiyah Covid-19 command center. This means that students and the Muhammadiyah Covid-19 Command Center